Determination Antimicrobial Activity from Ethanolic Extract of Mentha piperita L. (peppermint) - Hammadi, Amer Ali; Adnan, Hadeel (Scientific Journal of Medical Research, 2021)
Objectives: The current study aims to determine the inhibitory efficiency of alcoholic Mentha piperita L. extracts and investigate their effectiveness antimicrobial activities against different pathogenic bacteria. Methods: One solvent used is, ethanol to obtain of cured extract of M. piperita extraction ,which tested the effectiveness on four type of bacteria are (Klebsiella pneumonia , Escherichia coli, staphylococcus aureus and Streptococcus pneumonia ) to determine the most efficient concentration of solvent optimization, and then was determined minimum inhibitory concentration (MIC) of the extract more efficient. Results: The extract showed activity in vitro against four species of pathogenic bacteria (Escherichia coli, Klebsiella pneumonia , Staphylococcus aureus and Streptococcus pneumonia) compared with the antibiotic this appear in inhibition zone diameter for these four pathogenic bacteria (23,18, 9)mm, (12, 12, 10)mm,(17, 11)mm and (10, 8)mm in arrangement .All isolates were sensitive to ethanolic extracts of M. piperita and gram’s negative bacteria more effectiveness than gram’s positive. Conclusion: The current report will help in the isolation of new products/drugs. The results of this work have shown that M. piperita extracts possess compounds with antimicrobial and antioxidant properties.